Determinan Pengangguran Terdidik Jawa Timur - Mochamad Miftahul Huda; I. Wayan Subagiarta; Moh. Adenan (UPT Penerbitan Universitas Jember, 2018)
The main problem in this study is about the large number of educated unemployment that occurred in the province of East Java. This study aimed to describe the factors that influence the Educated Unemployment in East Java province. This type of research is explanatory research which kind of research that explains the relationship between the dependent variable and independent variables. Data collected documents, publications of the Central Bureau of Statistics. The results showed that the District Minimum Wage, Working Age Population, Gross Domestic Product has an effect on an Educated Unemployment in East Java.Keywords: Educated Unemployment, District Minimum Wage, Working Age Population , Regional Gross Domestic Product